Cortical modulation of resting state BOLD signals in white matter - Zhaohua Ding; Lyuan Xu; Yurui Gao; Yu Zhao; Yicheng Tan; Adam W. Anderson; Muwei Li; John C. Gore (Scientific Reports)
Abstract Magnetic resonance images of normal brains were analyzed in order to clarify the relationship of resting state BOLD signals in white matter to cortical neural activity. We quantified the degree to which spontaneous activities in the cortex, which are reflected in low frequency fluctuations in BOLD signals from gray matter, modulate corresponding resting state BOLD signals in white matter. The similarity between the resting state BOLD signals from selected cortical regions and white matter voxels, measured using the inner product of their time series, was found to be directly proportional to the BOLD signal power in each cortical volume. From measurements of resting state correlations we find cortical networks supporting more basic level functions tend to contribute more to correlated fluctuations in white matter than those of higher level functions. In addition, each cortical network exhibits a distinct spatial pattern of modulating effects on white matter BOLD signals, and their magnitudes are strongly correlated with the myelination level of the cortical network. Our findings confirm that resting state BOLD signals in white matter encode the spontaneous activity of specific cortical networks and are affected by the cytomyeloarchitecture of the cortex.